Early history of Asteraceae in Patagonia: Evidence from fossil pollen grains - Katinas, Liliana (2007)
The Asteraceae are classified into three subfamilies: Barnadesioideae, Cichorioideae, and Asteroideae. It has been suggested that the southern South American subfamily Barnadesioideae is the basal branch of the phylogenetic tree of the family, and Patagonia is the ancestral area of Asteraceae. Here we explore the chronological records of some members of the family, with findings of Mutisiinae (tribe Mutisieae, subfamily Cichorioideae) from the Late oligocene (28–23 Ma) and of Barnadesioideae and Nassauviinae (Mutisieae) from the early Miocene (23–20 Ma), all recovered from marine deposits of Patagonia. even though the succession of fossil appearances (first Mutisieae) differs from that provided by molecular data (first Barnadesioideae), this new scheme offers additional evidence towards the understanding of the early history of ancestral Asteraceae.